Design and Explanation of a Model for Managing Difficult Employees in Human Resource Managers of the Housing Foundation of the Islamic Revolution - Khalili Samani , Mohsen; Dalvi , Mohammad Reza; shirvani , Alireza (Management Strategies and Engineering Sciences, 2025)
This study aims to design and explain a comprehensive model for managing difficult employee behaviors in the Housing Foundation of the Islamic Revolution. The significance of this topic lies in the negative impacts of difficult behaviors on productivity, team morale, and organizational culture. Accordingly, by focusing on identifying and analyzing difficult behaviors, the study seeks to provide practical solutions for human resource managers to help reduce organizational tensions and improve the workplace environment. This research employs a mixed-methods approach (qualitative and quantitative). In the qualitative phase, semi-structured interviews with human resource managers were analyzed, and relevant findings were extracted. In the quantitative phase, data were collected using standardized questionnaires and analyzed through factor analysis and hypothesis testing. The results highlighted the importance of implementing managerial strategies to mitigate toxic behaviors and enhance constructive interactions. Solutions such as conducting constructive feedback sessions, improving communication processes, and training stress management were among the most effective measures identified in the study. These initiatives, by strengthening team culture and transparency in communication, facilitate the reduction of tensions and increase employee engagement and commitment. Statistical tests also indicated that variables such as explicit honesty and social awareness have the most significant impact on improving organizational behaviors. Ultimately, this study emphasizes that managing difficult organizational behaviors requires a comprehensive and multidimensional approach. The findings underscore the importance of continuous monitoring and evaluation, organizational training, and the application of effective leadership to create a positive work environment and reduce negative behaviors. By identifying key factors and providing practical strategies, this research contributes to the existing body of knowledge on managing toxic organizational behaviors and offers guidance for managers and organizational policymakers.